ISSUES CONTRIBUTING TO LOW PERFORMANCE OF ENGLISH IN A NATIONAL SCHOOL IN SONG, SARAWAK - Louis Cheng; Melor Md. Yunus; Maslawati Mohamad (Proceedings of The ICECRS, 2016)
English is becoming more important in this globalized world. In Malaysia, calls have been made from rulers and commoners alike to use English as the primary medium of instruction in primary schools. Although Malaysia has centralized education system for every state, rural schools might be in danger of losing out to their counterparts in the urban areas. Numerous programmes have been done to bring the standard of English in the school up to par with their counterparts from urban schools and yet English remains a tricky subject to master. In a rural school in the district of Song, Sarawak, English has always been the lowest performing subjects in UPSR year after year. Parallel to UPSR, the pupils for English intervention programme (LINUS BI) has the most compared to Bahasa Malaysia (BM) and Mathematics. This paper will attempt to research and understand the primary issues contributing to low performance of English in the school. At the same time, this paper will attempt to compare the background of pupils with high performance of English and pupils with low and mediocre performance in English and the causes leading to what they are today.